APPLICATION OF QUALITY FUNCTION DEPLOYMENT ON PRACTICUM NEEDS ANALYSIS OF MECHANICAL ENGINEERING EDUCATION PROGRAM, PALANGKA RAYA UNIVERSITY - Wiyogo; Yesni Nopy (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2014)
Laboratory role in engineering education is very important because it provides the experience and to deepen skills. Therefore the quality of practical implementation needs to get attention. From the observation of the students as respondents, seven (7) things as the main target can be obtained. From those 7 things obtained, there are eight (8) technical parameters that can be interacted each other. Positive parameter interaction on technical response relationship 1 to 3, on the proposal of additionals and improvements of laboratory buildings/rooms also closely related to the practical needs. Positive interaction is also shown in relation 3 and 7, the submission of practicum needs must be adjusted to the job sheet of activities conducted. Based on the results of these interactions, it can be seen that the highest contribution is the preparation of the job sheet with the target of the suitability the learning and implementation of training with a value of 22.7 %. The first priority to be changed is the skills of lecturers/laboratory staffs to demonstrate a tool skill that has mounted to 18.59% and the second priority is the suitability of training with the class courses with the value of 18.33.